Contemporary painting based on the philosophical meaning of Surakarta Classical Batik / Adam Wahida and Endang Sri Handayani - Wahida, Adam; Sri Handayani, Endang (Faculty of Art and Design, 2019)
This article is a result of a study to create contemporary paintings that have a local identity and character. The ideas of paintings creation are based on the philosophical meaning of Surakarta classical batiks, such as Sidoasih, Sidomukti and Sidoluhur which teach noble guidance about the life expectancy, existence, establishment, behavior and glory. Material related to forms and philosophical meanings is developed and linked to life today. The method of painting creation uses development research with steps that are namely: (1) information collecting, (2) development of the preliminary product, (3) preliminary product testing, (4) main product revision and (5) main field testing. The results of the study are contemporary paintings with a symbolic approach created using block, brushstroke and drip techniques on mixed media. The ideas behind paintings produced are representatives of the philosophical meanings of classical batik of Surakarta that are adapted to current life.